The Effect of Pin Length and Compressive Force in Double Side Friction Stir Welding on Bending Strength of AA1100 - Sukma Satriawan; Setiawan, Agus; Pebrianti, Dwi; Binti MD. Zain, Zainah (Evrimata: Journal of Mechanical Engineering, 2024)
Many new welding methods have emerged to improve connection results, including friction stir welding (FSW). FSW is a welding method that is widely used in welding aluminium alloys. FSW method on AA1100 aluminium material has not yet obtained the maximum bending strength so it is necessary to study the improvement of the quality of FSW joints using the welding method on both sides or double side friction stir welding (DFSW). This study aims to determine the effect of pin length and downward force on double side friction stir welding (DFSW) on the bending strength of AA1100 aluminium . The independent variables of this study are pin length (1.5 mm, 2 mm, 2.5 mm) and downward force (30 kg, 35 kg, 40 kg, 45 kg). The controlled variables are shoulder diameter of 25 mm, machine table translational speed of 10 mm/min, spindle rotation speed of 1750 rpm, base plate temperature of 250ºC, and AA1100 plate thickness of 3.6 mm with butt joint type welding connection model. The method used in this research is experimental using the factorial design of experiment (DOE) data analysis method. The results of this study indicate that pin length and downward force have a significant effect on the bending strength of DFSW welded joints on AA1100. The maximum bending strength value of the welded joint was 289.59 MPa at a pin length variation of 2 mm and a compressive force of 35 kg. The percentage of weld defects including tunnel and flash in welded joints with maximum bending strength is identified as the least and the micro test results also show the least FeAl3 particle grains.